Active and passive smoking and risk of ulcerative colitis: A case–control study in Japan. Issue 4 (13th December 2021) - Nishikawa, Atsushi; Tanaka, Keiko; Miyake, Yoshihiro; Nagata, Chisato; Furukawa, Shinya; Andoh, Akira; Yokoyama, Tetsuji; Yoshimura, Naoki; Mori, Kenichiro; Ninomiya, Tomoyuki; Yamamoto, Yasunori; Takeshita, Eiji; et al.
Abstract: Background and Aim: Although an inverse relationship between current smoking and the development of ulcerative colitis (UC) has been shown in North America and Europe, evidence is limited in Asian countries, where the incidence of UC is rapidly increasing. This Japanese case–control study examined the association between active and passive smoking and risk of UC. Methods: A self‐administered questionnaire was used to obtain information on smoking and potential confounding factors in 384 cases with a diagnosis of UC within the past 4 years and 665 controls. Results: Compared with having never smoked, having ever smoked was associated with an increased risk of UC (adjusted odds ratio [OR] = 1.70, 95% confidence interval [CI]: 1.23–2.37). No association was observed between current smoking and risk of UC, but former smokers had a significant elevation in risk (adjusted OR = 2.40, 95% CI: 1.67–3.45). There was a positive dose–response relationship with pack‐years smoked ( P for trend = 0.006). Among never smokers, passive smoking exposure at home was significantly associated with an increased risk of UC (adjusted OR = 1.90, 95% CI: 1.30–2.79). A significant dose–response gradient was also observed between pack‐years of passive smoking at home and risk of UC ( P for trend = 0.0003). Conclusions: We confirmed that former smoking elevated the risk of UC, whereas an inverse association between current smoking and the risk of UC did not reach a statistically significant level. Passive smoking may be associated with an increased risk of UC.